Effect of Ascorbic Acid, Activated Charcoal and Dark Incubation on Browning Intensity of Saurauia bracteosa In Vitro Culture - Putri Octaviana Ginting, Naomi Bastanta; Restiani, Ratih; Prasetyaningsih, Aniek; Meyga Semarayani, Cokorda Istri (Biosaintifika: Journal of Biology & Biology Education, 2023)
Saurauia bracteosa, also known as Pirdot, is an endemic woody plant of the Actinidiaceae family with medicinal properties. Its population decline in nature has led to a vulnerable status, prompting conservation efforts, such as in vitro culture. Browning poses a significant challenge in the woody plant in vitro culture. Browning inhibitors such as ascorbic acid, activated charcoal and dark incubation can be used to address this issue. This study aims to determine the effect of ascorbic acid, activated charcoal and incubation conditions on browning inhibition of S.bracteosa. The study employed a Completely Randomized Design with 12 treatments on leaf explants, repeated five times. Observations, including the time of browning formation, percentage of browning, intensity of browning and percentage of live explant were carried out for 30 days and analyzed using ANOVA followed by DMRT. The results showed that the addition of activated charcoal in MS media with dark incubation delayed the browning formation time (12.40 DAI) while the adding ascorbic acid in MS media and dark incubation resulted in the lowest browning intensity (0.22). These research findings can serve as a foundational protocol for browning prevention, supporting the successful in vitro conservation of S. bracteosa.